Pemanfaatan Limbah Spent Bleaching Earth (SBE) untuk Beton Ringan sebagai Material Konstruksi yang Ramah Lingkungan: Utilization of Spent Bleaching Earth (SBE) Waste for Lightweight Concrete as Ecofriendly Construction Materials - AGUNG SUMARNO; AGUS MUDO PRASETYO (Jurnal Teknologi Lingkungan, 2022)
ABSTRACT Lightweight concrete as a non-structural construction material to replace brick is commonly used because it has a lighter mass and is more practical in installation. This research utilizes Spent Bleaching Earth (SBE) waste as a substitute for sand in the manufacture of lightweight concrete using the Non-Autoclaved Aerated Concrete (NAAC) method with variations in the addition of Al as aerating compounds (0.20% and 0.25% by mass of cement). The NAAC method was chosen because the process is more energy-efficient when compared to the Autoclaved Aerated Concrete (AAC) method. The alkalinity of this lightweight concrete mixture is controlled by adding lime to a certain amount. In the sample with an Al content of 0.20%, the minimum density results were obtained 785.95 kg/m3 (B0A) and a maximum of 1,313.73 kg/m3 (B5A). In contrast, Al content of 0.25% the minimum density results was obtained 781.37 kg/m3 (B0B) and maximum 1,256.89 kg/m3 (B5B). Measurement of water absorption in the sample with an Al content of 0.20% obtained a minimum result of 2.51% (B5A) and a maximum of 40.74% (B0A). Meanwhile, the sample with an Al content of 0.25% obtained a minimum yield of 2.91% (B5B) and a maximum of 43.97% (B0B). Compressive strength calculation of concrete with 28 days old in a sample with an Al content of 0.20%, a minimum result of 1.15 MPa (B0A) and a maximum of 2.95MPa (B5A) is obtained, whereas for a sample with an Al content of 0.25%, a minimum result of 0.77 MPa (B0B) and a maximum of 2.43 Mpa (B5B) is obtained. The flexural strength of lightweight concrete, aged 28 days in samples with 0.20% Al content, obtained a minimum result of 0.67 MPa (B0A) and a maximum of 1.31 MPa (B3A). In contrast, samples with an Al content of 0.25% obtained a minimum of 0.73 MPa (B0B) and a maximum of 1.28 MPa (B3B). Keywords : Lightweight concrete, NAAC, Spent Bleaching Earth, Ecofriendly ABSTRAK Pemanfaatan beton ringan sebagai material konstruksi non struktural pengganti batu bata merah sudah sangat umum digunakan karena memiliki massa yang lebih ringan dan lebih praktis dalam pemasangan. Penelitian ini memanfaatkan limbah Spent Bleaching Earth (SBE) sebagai pengganti pasir dalam pembuatan beton ringan menggunakan metode Non Autoclaved Aerated Concrete (NAAC) dengan variasi penambahan senyawa pengaerasi Al (0,20% dan 0,25% berat semen).  Metode NAAC dipilih karena prosesnya lebih hemat energi bila dibandingkan dengan metode Autoclaved Aerated Concrete (AAC). Alkalinitas campuran beton ringan ini dikontrol dengan penambahan kapur sampai jumlah tertentu. Pada sampel dengan kadar Al 0,20% diperoleh hasil densitas minimal 785,95 kg/m3 (B0A) dan maksimal 1.313,73 kg/m3 (B5A) sedangkan pada kadar Al 0,25% diperoleh hasil densitas minimal 781,37 kg/m3 (B0B) dan maksimal 1.256,89 kg/m3 (B5B). Pengukuran penyerapan air pada sampel dengan kadar Al 0,20% diperoleh hasil minimal 2,51% (B5A) dan maksimal 40,74% (B0A), sedangkan pada sampel dengan kadar Al 0,25% diperoleh hasil minimal 2,91% (B5B) dan maksimal 43,97% (B0B). Perhitungan kuat tekan beton umur 28 hari pada sampel dengan kadar Al 0,20% diperoleh hasil minimal 1,15 MPa (B0A) dan maksimal 2,95 MPa (B5A), sedangkan pada sampel dengan kadar Al 0,25% diperoleh hasil minimal 0,77 MPa (B0B) dan maksimal 2,43 Mpa (B5B). Kuat lentur beton ringan umur 28 hari pada sampel dengan kadar Al 0,20% diperoleh hasil minimal 0,67 MPa (B0A) dan maksimal 1,31 MPa (B3A), sedangkan pada sampel dengan kadar Al 0,25% diperoleh hasil minimal 0,73 MPa (B0B) dan maksimal 1,28 MPa (B3B). Kata Kunci : Beton Ringan, NAAC, Spent Bleaching Earth, Ramah Lingkungan